Amino-terminal Pro-B-Type Natriuretic Peptide Among Patients Living With Both Human Immunodeficiency Virus and Heart Failure. (28th September 2019) - Alvi, Raza M; Zanni, Markella V; Neilan, Anne M; Hassan, Malek Z O; Tariq, Noor; Zhang, Lili; Afshar, Maryam; Banerji, Dahlia; Mulligan, Connor P; Rokicki, Adam; Awadalla, Magid; Januzzi, James L; et al.
Abstract: Background: Among persons living with human immunodeficiency virus (PHIV), incident heart failure (HF) rates are increased and outcomes are worse; however, the role of amino-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations among PHIV with HF has not been characterized. Methods: Patients were derived from a registry of those hospitalized with HF at an academic center in a calender year. We compared the NT-proBNP concentrations and the changes in NT-proBNP levels between PHIV with HF and uninfected controls with HF. Results: Among 2578 patients with HF, there were 434 PHIV; 90% were prescribed antiretroviral therapy and 62% were virally suppressed. As compared to controls, PHIV had higher admission (3822 [IQR, 2413–7784] pg/ml vs 5546 [IQR, 3257–8792] pg/ml, respectively; P < .001), higher discharge (1922 [IQR, 1045–4652] pg/ml vs 3372 [IQR, 1553–5452] pg/ml, respectively; P < .001), and lower admission-to-discharge changes in NT-proBNP levels (32 vs 48%, respectively; P = .007). Similar findings were noted after stratifying based on left ventricular ejection fraction (LVEF). In a multivariate analysis, cocaine use, a lower LVEF, a higher NYHA class, a higher viral load (VL), and a lower CD4 count were associated with higher NT-proBNP concentrations. In follow-up, among PHIV, a higher admission NT-proBNP concentration was associated with increased cardiovascular mortality (first tertile, 11.5; second tertile, 20; third tertile, 44%; P < .001). Among PHIV, each doubling of NT-proBNP was associated with a 19% increased risk of death. However, among patients living without HIV, each doubling was associated with a 27% increased risk; this difference was attenuated among PHIV with lower VLs and higher CD4 counts. Conclusions: PHIV with HF had higher admission and discharge NT-proBNP levels, and less change in NT-proBNP concentrations. Among PHIV, VLs and CD4 counts were associated with NT-proBNP concentrations; in follow-up, higher NT-proBNP levels among PHIV were associated with cardiovascular mortality. Abstract : Persons living with human immunodeficiency virus (PHIV) hospitalized with heart failure (HF) had higher admission and discharge amino-terminal pro-B-type natriuretic peptide (NT-proBNP), and lower NT-proBNP concentration change. Among PHIV, higher viral load and lower CD4 count were associated with NT-proBNP. In follow-up, higher NT-proBNP among PHIV with HF was associated with cardiovascular mortality.